Phonological errors in the pronunciation of Indonesian nasal consonants by native Arabic speakers - Hasana, Nurul; Subiyanto, Agus (LingTera, 2025)
This descriptive qualitative study investigates pronunciation errors in Indonesian nasal consonants made by native Arabic speakers. Using a reading elicitation technique, data were collected focusing on the pronunciation of the nasal consonants /ŋ/ and /ɲ/, which were then transcribed using International Phonetic Alphabet (IPA) symbols. The analysis involved identifying distinctive features of sounds within the nasal segment when errors occurred. The results revealed a consistent pattern of assimilation, with changes notably influenced by surrounding sounds. Velar nasals underwent assimilation influenced by both vowels and consonants, resulting in substitutions such as /ʔ/, /ɢ/, and /n/. In contrast, palatal nasals showed assimilation primarily influenced by adjacent vowels, leading to alterations represented by /ʔ/ and /ɲj/. These findings highlight the systematic nature of phonological errors in the pronunciation of nasal consonants by Arabic speakers learning Indonesian and offer valuable insights for language instructors and researchers in the field of second language acquisition.